Interface Engineering of Titanium Nitride Nanotube Composites for Excellent Microwave Absorption at Elevated Temperature - Li, Cuiping; Li, Dan; Zhang, Shuai; Ma, Long; Zhang, Lei; Zhang, Jingwei; Gong, Chunhong (Nano-Micro Letters, 2024)
Currently, the microwave absorbers usually suffer dreadful electromagnetic wave absorption (EMWA) performance damping at elevated temperature due to impedance mismatching induced by increased conduction loss. Consequently, the development of high-performance EMWA materials with good impedance matching and strong loss ability in wide temperature spectrum has emerged as a top priority. Herein, due to the high melting point, good electrical conductivity, excellent environmental stability, EM coupling effect, and abundant interfaces of titanium nitride (TiN) nanotubes, they were designed based on the controlling kinetic diffusion procedure and Ostwald ripening process. Benefiting from boosted heterogeneous interfaces between TiN nanotubes and polydimethylsiloxane (PDMS), enhanced polarization loss relaxations were created, which could not only improve the depletion efficiency of EMWA, but also contribute to the optimized impedance matching at elevated temperature. Therefore, the TiN nanotubes/PDMS composite showed excellent EMWA performances at varied temperature (298–573 K), while achieved an effective absorption bandwidth (EAB) value of 3.23 GHz and a minimum reflection loss (RLmin) value of − 44.15 dB at 423 K. This study not only clarifies the relationship between dielectric loss capacity (conduction loss and polarization loss) and temperature, but also breaks new ground for EM absorbers in wide temperature spectrum based on interface engineering. Highlights: 1 The boosted heterogeneous interfaces in titanium nitride (TiN) nanotube/polydimethylsiloxane (PDMS) composite contributed to strong polarization loss relaxation ability. 2 The TiN nanotubes/PDMS composite possessed both good impedance matching behavior and strong dielectric loss ability in wide temperature spectrum. 3 The TiN nanotubes/PDMS composite exhibited excellent EMWA performances (effective absorption bandwidth value of 3.23 GHz and minimum reflection loss value of − 44.15 dB) at the varied temperature from 298 to 573 K.